2010
DOI: 10.1001/archoto.2009.179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dysplasia in Juvenile-Onset Recurrent Respiratory Papillomatosis

Abstract: Dysplasia is a rare event in pediatric recurrent respiratory papillomatosis, and there does not appear to be an association between the use of cidofovir and dysplastic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
(20 reference statements)
3
17
0
Order By: Relevance
“…In juvenile-onset RRP group eight cases showed signs of only histologically evident keratosis, including one case of slight epithelium dysplasia (16 years old girl). These findings correspond with the data of literature that dysplasia is a rare event in pediatric RRP [33].…”
Section: Patientssupporting
confidence: 92%
“…In juvenile-onset RRP group eight cases showed signs of only histologically evident keratosis, including one case of slight epithelium dysplasia (16 years old girl). These findings correspond with the data of literature that dysplasia is a rare event in pediatric RRP [33].…”
Section: Patientssupporting
confidence: 92%
“…In this setting it is typically administered as an intravenous infusion, where it is known to cause nephrotoxicity, hepatic dysfunction, hematopoietic dysfunction, and ocular toxicity 8. Although case reports have raised concern for carcinogenicity,9 histologic studies of human specimens have shown no evidence to support this relationship 10–12. Prior surveys and case series have estimated that 2% to 3% of patients with RRP develop squamous cell carcinoma of the upper aerodigestive tract2; however, this appears to be equivalent in patients with and without exposure to cidofovir 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Its treatment efficacy can be as high as 80% (according to RRPF; see Table I). Due to the risk of nephro-and hepatotoxicity (according to Sajan et al [8]), the treatment is recommended for patients with a history of severe and resistant disease. The efficacy of cidofovir and its side effects have been discussed in Europe for some time.…”
Section: Discussionmentioning
confidence: 99%